2014
DOI: 10.1002/anie.201404397
|View full text |Cite
|
Sign up to set email alerts
|

A Protein‐Based Pentavalent Inhibitor of the Cholera Toxin B‐Subunit

Abstract: Protein toxins produced by bacteria are the cause of many life-threatening diarrheal diseases. Many of these toxins, including cholera toxin (CT), enter the cell by first binding to glycolipids in the cell membrane. Inhibiting these multivalent protein/carbohydrate interactions would prevent the toxin from entering cells and causing diarrhea. Here we demonstrate that the site-specific modification of a protein scaffold, which is perfectly matched in both size and valency to the target toxin, provides a conveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 34 publications
2
65
0
Order By: Relevance
“…Through the creation of excellent multivalent binders that match the topology of the receptor protein structure, e.g., starfish-like inhibitors, a deeper understanding of multivalency was gained. [104][105][106][107][108]109 . These molecules with their planar and radially distributed binding sites have shown their potency to block the interaction of planar homopentameric subunits present in bacterial toxins like Cholera and Shiga.…”
Section: Ligand Densitymentioning
confidence: 99%
“…Through the creation of excellent multivalent binders that match the topology of the receptor protein structure, e.g., starfish-like inhibitors, a deeper understanding of multivalency was gained. [104][105][106][107][108]109 . These molecules with their planar and radially distributed binding sites have shown their potency to block the interaction of planar homopentameric subunits present in bacterial toxins like Cholera and Shiga.…”
Section: Ligand Densitymentioning
confidence: 99%
“…Thermo-responsive polymers, such as poly(N-isopropyl acrylamide) (PNIPAM), undergo a reversible phase transition from hydrophilic to hydrophobic when their solution temperature is raised above their LCST, changing from an extended chain conformation below LCST into a collapsed chain above LCST. 6,[32][33][34][35][36][37] In general, the interaction of a lectin with a carbohydrate is quite weak, but can be dramatically enhanced by the multivalent effect of glycopolymers, which is known as the "glycocluster Scheme 1 Synthesis of the triblock copolymer by sequential RAFT polymerization and its host-guest interaction with self-assembly behaviour. In general, the LCST of PNIPAM can be influenced by several factors, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1 This has demonstrated that the multivalent presentation of a particular glycotope on an appropriate scaffold (i.e. [2][3][4][5][6][7][8][9][10][11][12][13] Indeed, the promise that specic lectin-mediated processes (i.e., pathogen recognition, viral entry, tumor migration and metastasis events, etc.) can affect signicantly its potency and selectivity of binding with a given target protein, relative to that of a monovalent counterpart.…”
Section: Introductionmentioning
confidence: 99%